2020
DOI: 10.3390/app10082912
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Daily Activity Plans of Travelers Using the Park-and-Ride System and Autonomous Vehicles: Work and Shopping Trip Purposes

Abstract: The preferences of travelers determines the utility of daily activity plans. Decision-makers can affect the preference of travelers when they force private car users to use park-and-ride (P&R) facilities as a way of decreasing traffic in city centers. The P&R system has been shown to be effective in reducing uninterrupted increases in traffic congestion, especially in city centers. Therefore, the impacts of P&R on travel behavior and the daily activity plans of both worker and shopper travelers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
(39 reference statements)
0
23
0
3
Order By: Relevance
“…The scenarios of group (a) are (1) travellers who travel more than 40 minutes within one trip including the users of all transport modes, (2) travellers who travel more than 40 minutes excluding users of walking and cycling, and (3) travellers who travel at least 10 km in one trip, regardless of transport mode type. Scenarios of group (b) are (4) AVs as a feeder system from home to the nearest public transport stop, and from public transport stop home replace four conventional cars and a study conducted in Hungary showed that the workers and shoppers who use park-and-ride system, would use AVs instead of their conventional cars [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…The scenarios of group (a) are (1) travellers who travel more than 40 minutes within one trip including the users of all transport modes, (2) travellers who travel more than 40 minutes excluding users of walking and cycling, and (3) travellers who travel at least 10 km in one trip, regardless of transport mode type. Scenarios of group (b) are (4) AVs as a feeder system from home to the nearest public transport stop, and from public transport stop home replace four conventional cars and a study conducted in Hungary showed that the workers and shoppers who use park-and-ride system, would use AVs instead of their conventional cars [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…As is widely considered, P & R systems have played an essential role in the encouragement of the shift of passengers from private vehicles to public transportation [12,13,[15][16][17][18][19][20][21]. Therefore, the facility's location is close to the public transport system stops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors have contributed to research on the Park and Ride system in a project called "An integrated study of Park and Ride (P & R) facilities for sustainable urban mobility". The previous research already published corresponds to the interaction of conventional and autonomous vehicles with the Park and Ride system [12], in addition to the development of an integral model of the P & R system that allows for the determination of which facility is the most attractive based on the potential demand [13]. Moreover, multi-criteria methods were used to determine a facility location problem and in which experts determined that the criteria of accessibility to public transportation is the most important when implementing a P & R system [14].…”
Section: Introductionmentioning
confidence: 99%
“…This article is part of a project where the authors work to investigate a P&R system and its different variables; thus, the authors have already made previous publications as part of an integrated analysis of P&R [15][16][17]. Consequently, transport specialists have started to use multi-criteria decision-making applications (MCDM) to provide solutions to issues and increase the quality for citizens through transport initiatives.…”
Section: Criteria Sub Criteriamentioning
confidence: 99%